Avaliação por ressonância magnética de massas cardíacas = Magnetic resonance imaging evaluation of cardiac masses - Braggion-Santos, Maria F.; Koenigkam-Santos, Marcel; Teixeira, Sara Reis; Volpe, Gustavo Jardim; Trad, Henrique Simão; Schmidt, André (Arquivos brasileiros de cardiologia, 2013)
Background - Cardiac tumors are extremely rare; however, when there is clinical suspicion, - proper diagnostic evaluation is necessary to plan the most appropriate treatment. - In this context, cardiovascular magnetic resonance imaging (CMRI) plays an - important role, allowing a comprehensive characterization of such lesions. - - Objective - To review cases referred to a CMRI Department for investigation of cardiac and - paracardiac masses. To describe the positive case series with a brief review of - the literature for each type of lesion and the role of cardiovascular magnetic - resonance imaging in evaluation. - - Methods - Between August 2008 and December 2011, all cases referred for CMRI with suspicion - of tumor involving the heart were reviewed. Cases with positive histopathological - diagnosis, clinical evolution or therapeutic response compatible with the clinical - suspicion and imaging findings were selected. - - Results - Among the 13 cases included in our study, eight (62%) had histopathological - confirmation. We describe five benign tumors (myxomas, rhabdomyoma and fibromas), - five malignancies (sarcoma, lymphoma, Richter syndrome involving the heart and - metastatic disease) and three non-neoplastic lesions (pericardial cyst, - intracardiac thrombus and infectious vegetation). - - Conclusion - CMRI plays an important role in the evaluation of cardiac masses of non-neoplastic - and neoplastic origin, contributing to a more accurate diagnosis in a noninvasive - manner and assisting in treatment planning, allowing safe clinical follow-up with - good reproducibility.